Evaluation of Romania’s Progress in Achieving SDG 11: Sustainable Cities and Communities - ALPOPI Cristina; BURCEA Ștefan-Gabriel; POPESCU Ruxandra-Irina; BURLACU Sorin (Applied Research in Administrative Sciences)
The article evaluates the progress made by Romania in order to achive the sustainable development goal regarding sustainable cities and communities (SDG 11). The 10 indicators and targets associated with SDG 11 are taken into account from the point of view of the evolution recorded by Romania in the period 2010-2020. This exploratory study aims to analyse secondary data collected from the Eurostat platform dedicated to SDG-related indicators. Thus, we aim to track the extent to which Romania has progressed toward achieving each target associated with SDG 11 and to identify the target(s) for which progress has been most significant.